Bioequivalence of Alendronate and Vitamin D3 in a Combination Tablet Versus Corresponding-Dose Individual Tablets in Healthy Taiwanese Volunteers, Determined Using a Novel Plasma Alendronate Assay - D. Hamish Wright, PhD; Ramon Mols, BSc; Kevin R Brown, BA; Geng-Chang Yeh, MD, PhD; Eric Woolf, PhD; Lisa Hickey, MS; Stefan Zajic, PhD (Elsevier, 2015)
Objective: This study was designed to demonstrate that alendronate (ALN)/vitamin D3 combination tablets (ALN/D5600) are bioequivalent to corresponding doses of ALN and vitamin D3 as individual tablets in healthy Taiwanese volunteers. Methods: In this open-label, randomized, 2-period, crossover study, 68 volunteers were randomized to a single ALN/D5600 combination tablet or corresponding doses of 70 mg ALN + 5600 IU vitamin D3 (2 × 2800 IU), followed by a 12-day washout period and administration of the alternate formulation. Plasma ALN levels were measured using a newly developed assay. Geometric mean ratios of ALN AUC0-last, AUC0-∞, and Cmax, and unadjusted vitamin D3 AUC0-80h and Cmax were compared and considered bioequivalent if the 90% CI was within 0.8 to 1.25. Results: The geometric mean ratios were: AUC0-last, 1.084 (90% CI, 0.937-1.253); AUC0-∞, 1.081 (90% CI, 0.935-1.249); and Cmax, 1.112 (90% CI, 0.959-1.289) for ALN, and AUC0-80h 0.953 (90% CI, 0.827-1.098) and Cmax, 0.982 (90% CI, 0.854-1.130) for vitamin D3 unadjusted for endogenous levels. Conclusions: The combination tablet was considered bioequivalent to coadministration based on ALN AUC0-∞ and unadjusted vitamin D3 parameters. Slight differences for ALN AUC0-last and Cmax (upper 90% CIs outside the bounds) were not considered clinically significant. The combination tablet was well tolerated. No serious adverse experiences were reported. © 2015. The Authors. Published by Elsevier Inc. All rights reserved.